Beliefs, Attitudes and values of mothers related to Childhood and Child Labor in Lima - Simón, Ana (2020)
The present research sought to identify and analyze the beliefs and attitudes towards childhood and child labor and the association with individual values of mothers from the districts of Villa El Salvador and San Juan de Lurigancho in Lima Metropolitana. Twelve mothers were interviewed using a semi-structured interview. Results indicate that participants link childhood with characteristics and activities related primarily to recreation and education. Likewise, they evaluate child labor in a negative and ambivalent way, which is influenced by living in an unsafe context. Their beliefs and attitudes towards childhood and child labor are rooted in values such as work, progress, responsibility and filiation.